2017
DOI: 10.1016/j.parkreldis.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Tai Chi and Qigong mind-body exercises on motor and non-motor function and quality of life in Parkinson's disease: A systematic review and meta-analysis

Abstract: Purpose To systematically evaluate and quantify the effects of Tai Chi/Qigong (TCQ) on motor (UPDRS III, balance, falls, Timed-Up-and-Go, and 6-Minute Walk) and non-motor (depression and cognition) function, and quality of life (QOL) in patients with Parkinson’s disease (PD). Methods A systematic search on 7 electronic databases targeted clinical studies evaluating TCQ for individuals with PD published through August 2016. Meta-analysis was used to estimate effect sizes (Hedge’s g) and publication bias for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 77 publications
5
126
0
11
Order By: Relevance
“…Using the Unified Parkinson's disease rating scale-motor section (UPDRS-III) as an evaluation tool, one study reported that Qigong plus medication had better effects than medication alone, nevertheless without statistically significant differences; another study reported that Qigong plus medication was not much different than medication alone in gait velocity or step length; and a third study assessing the quality of life in patients using the PDQ-39 instrument, reported that Qigong plus medication showed better effects than aerobic exercise plus medication [39]. Song et al (2017) showed that Taijiquan and Qigong may improve the motor function, balance, timed up and go, 6 min walk, falls, as well as depression and quality of life in individuals with PD, however these authors highlight the fact that additional large-scale trials are needed [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Unified Parkinson's disease rating scale-motor section (UPDRS-III) as an evaluation tool, one study reported that Qigong plus medication had better effects than medication alone, nevertheless without statistically significant differences; another study reported that Qigong plus medication was not much different than medication alone in gait velocity or step length; and a third study assessing the quality of life in patients using the PDQ-39 instrument, reported that Qigong plus medication showed better effects than aerobic exercise plus medication [39]. Song et al (2017) showed that Taijiquan and Qigong may improve the motor function, balance, timed up and go, 6 min walk, falls, as well as depression and quality of life in individuals with PD, however these authors highlight the fact that additional large-scale trials are needed [10].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence-based treatment strategies used in the management of some aspects of the disease include different forms of exercise, such as cycling [7,8], walking, strength, balance and flexibility routines [9], as well as physiotherapy [2]. Indeed, a growing body of evidence supports the role of exercise, among which are dancing, Qigong and Taijiquan, to improve both motor and non-motor symptoms in PD patients [10][11][12]. Indeed, physical exercise has been shown to improve not only balance, gait, mobility and reduction of falls, but also apathy, fatigue, depression, sleep disturbance and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…54,55 Reduction of overall distress and improved long-term prognosis is also supported by improvements in broader constructs including overall QOL 44,46 and selfe cacy. 26,47,56 While Qigong is increasingly being used to help manage health and distress in caregivers, including at leading academic medical centers like MD Anderson Cancer Center and Harvard's Dana-Farber Cancer Institute, we are not aware of any studies to date evaluating Qigong for caregivers.…”
Section: Qigong As a Promising Multimodal Intervention For Caregiversmentioning
confidence: 99%
“…Darüber hinaus werden in der PTK Einführungskurse in Techniken zur Stressbewältigung angeboten, z. B. nach Kaluza, Autogenes Training, Yoga, Tai Chi sowie LSVT ® BIG oder Musiktherapie, die nachweislich die motorischen und nichtmotorischen Funktionen verbessern [13][14][15][16]. Ziel ist es, Patienten zu motivieren, ausgewählte Verfahren im Alltag regelmäßig therapeutisch zu nutzen.…”
Section: Vor-/ Nachteile Des Ptk-konzepts Gegenüber Ambulanten Behandunclassified